Altered neurovascular control of the resting circulation in human metabolic syndrome - Limberg, Jacqueline K (Blackwell Science Inc, 2012)
Young healthy adults exhibit an inverse linear relationship between muscle sympathetic nerve activity (MSNA) and α-adrenergic responsiveness. This balance may be reversed in metabolic syndrome (MetSyn) as animal models exhibit increased sympathetic activity and α-mediated vasoconstriction. We hypothesized humans with MetSyn would demonstrate increased α-adrenergic vasoconstriction and the inverse relationship between MSNA and adrenergic responsiveness would be lost. We measured MSNA (microneurography of the peroneal nerve) and forearm blood flow (FBF, Doppler ultrasound) in 16 healthy control subjects (31 ± 3 years) and 14 adults with MetSyn (35 ± 3 years; P > 0.05) during local administration of α-adrenergic agonists (phenylephrine (PE), α(1); clonidine (CL), α(2)). MSNA was greater in MetSyn subjects than in healthy controls (P < 0.05). A group difference in vasoconstriction to PE was not detected (P= 0.08). The level of α(1)-mediated vasoconstriction was inversely related to MSNA in control subjects (r= 0.5, P= 0.04); this balance between MSNA and α(1) responsiveness was lost in adults with MetSyn. MetSyn subjects exhibited greater vasoconstriction to CL infusion as compared with healthy controls (P < 0.01). A relationship between MSNA and α(2)-mediated vasoconstriction was not detected in either group. In summary, altered neurovascular control in human MetSyn is receptor specific. The observed uncoupling between MSNA and α(1)-adrenergic responsiveness and increased α(2) vasoconstriction may lead to reduced FBF, altered flow distribution, and/or severe hypertension with the progression toward diabetes and cardiovascular disease.